Improving the Success of Culinary MSMEs through Product Innovation, Social Capital, and Digital Marketing: A Competitive Advantage Approach - Ahmad Taufiqurrahman Asy’ari; Naswan Suharsono; Madziatul Churiyah (Universitas Bina Sarana Informatika, 2026)
The increasingly competitive business environment encourages micro and small enterprises (MSEs) in the culinary sector to adapt through product innovation, strengthening social networks, and utilizing digital marketing to enhance business success. This study aims to analyze the effects of product innovation, social capital, and digital marketing on the business success of culinary-sector MSEs in Gresik Regency, as well as the role of competitive advantage as a mediating variable. This study employs a quantitative approach using a survey method and involves 377 respondents who are culinary MSE owners in Gresik Regency. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS) with SmartPLS 4. The results indicate that product innovation, social capital, and digital marketing have positive and significant effects on the business success of MSEs. Furthermore, these three variables also have positive and significant effects on competitive advantage. Competitive advantage is proven to have a positive and significant effect on business success and partially mediates the influence of product innovation, social capital, and digital marketing on business success. These findings confirm that the business success of MSEs depends not only on the availability of resources and marketing activities, but also on entrepreneurs’ ability to manage and transform innovation, social networks, and the use of digital marketing into sustainable competitive advantages that align with local market characteristics. This study provides practical implications for MSE owners and stakeholders in formulating integrated business development strategies to enhance competitiveness and business success in the culinary MSE sector.